Welcome Intrusions: Capturing the Unexpected in Translators’ Prefaces to Dante’s Divine Comedy - Feltrin-Morris, Marella (Tusaaji: A Translation Review, 2018)
As part of an ongoing research project, this essay examines a number of translators’ prefaces to Dante’s Divine Comedy, summarizing recurring patterns and then focusing on deviations from the norm. The majority of these prefaces tend to follow a script, particularly in the case of retranslations of classical texts, which require an acknowledgment of past translations, a homage to the authority of the source text and a display of the translator’s expertise. However, occasional detours from the predictable constellation of themes deserve closer scrutiny, since they give a more authentic voice to the individuals who engaged with the text in its deepest form, not merely within the confines of a prescriptive formula, but expanding the potential of this unique space towards new avenues of discovery.